PENGEMBANGAN FLIPBOOK INTERAKTIF TAT TWAM ASI UNTUK PEMAHAMAN IPAS SISWA KELAS VI SD BUSUNGBIU - Winaastari, Ni Putu Ayu; Handayani, Ni Nyoman Lisna; Winangun, I Made Ari (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2026)
Students’ understanding of Natural and Social Sciences (IPAS) concepts in elementary schools is still relatively low, partly due to the limited use of interactive and contextual learning media in the classroom. In addition, the integration of local wisdom values in science learning remains minimal, even though these values can strengthen students’ character and contextual understanding. Therefore, this study aims to develop interactive Flipbook learning materials that integrate the local wisdom value of Tat Twam Asi. The study also evaluates the validity, practicality, and effectiveness of the developed media in improving fifth-grade students’ conceptual understanding of IPAS. Using the ADDIE model—which comprises the phases of analysis, design, development, implementation, and evaluation—development research (R&D) is the methodology employed. To examine the effectiveness of the developed media, a pre-experimental design using a one-group pretest–posttest approach was employed. This design was used to measure students’ conceptual understanding before and after using the interactive flipbook. The research subjects consisted of media experts, material experts, language experts, fifth-grade teachers, and fifth-grade students from Elementary School Cluster 5 in Busungbiu District. This research is important because it evaluates the potential of integrating local wisdom values, such as Tat Twam Asi, into digital learning media to improve students’ conceptual understanding of science. Tests, observations, and questionnaires were employed as data gathering methods. With an average Aiken's V value above 0.88, the study's findings demonstrated the interactive Flipbook media's extremely high level of validity. Teachers and students responded very well to the practicality exam, with a proportion exceeding 90%. With an N-Gain value of 0.54, which falls into the medium-to-high range, the effectiveness test demonstrated an improvement in students' comprehension of IPAS principles. As a result, Tat Twam Asi's interactive Flipbook medium is deemed legitimate, useful, and efficient for use in primary school scientific instruction. Keywords: Interactive Flipbook, Tat Twam Asi, Science, Conceptual Understanding, Elementary School